Validation of C-Reactive Protein in early vs late onset neonatal sepsis and its correlation with blood culture in the diagnosis of neonatal sepsis - Paudel, L; Panthi, K; Marahatta, S (Devdaha Medical Journal, 2026)
Introduction: Neonatal sepsis is a major cause of morbidity and NICU admission, and early diagnosis is challenging due to nonspecific clinical features. Although blood culture is the gold standard, it has limitations such as low sensitivity, delayed results, and reduced yield after antibiotic exposure. This diagnostic gap highlights the role of adjunct biomarkers like C-Reactive Protein (CRP), which is rapid and requires smaller blood volume. This study aimed to validate CRP in early-onset (EONS) and late-onset neonatal sepsis (LONS) and assess its correlation with blood culture. Methods: This hospital-based prospective observational study was conducted at Devdaha Medical College from October 15, 2023, to October 14, 2025. Neonates with clinical suspicion of sepsis were included, while those with prior antibiotic exposure, congenital anomalies, or birth weight <1500 g were excluded. Blood culture (2 mL sample) was performed under aseptic conditions prior to antibiotics. CRP was measured at initial evaluation using a semi-quantitative latex agglutination method, with >10 mg/L considered positive. Statistical analysis was done using SPSS; chi-square test and diagnostic validity parameters were calculated. A p-value <0.05 was considered significant. Results: Among 253 neonates, 188 (74.3%) had EONS and 65 (25.7%) had LONS. CRP positivity was higher in LONS than EONS (49.2% vs 41.5%), but not statistically significant (p=0.347). Blood culture positivity was significantly higher in LONS (18.5% vs 5.9%, p=0.002). CRP showed sensitivity 69.8%, specificity 59.1%, PPV 14.5%, and NPV 95.1%. Sensitivity was higher in LONS (83.3%) than EONS (54.5%), while NPV remained high in both groups. ROC analysis showed AUC of 0.723 (p<0.001). Conclusion: CRP is a useful adjunct marker with high negative predictive value, making it valuable for ruling out neonatal sepsis. However, due to low specificity and PPV, it should not be used alone and must be interpreted with clinical findings and blood culture, particularly in late-onset sepsis. Keywords: Blood culture, c-reactive protein, early-onset sepsis, late-onset sepsis, neonatal sepsis.